Physicsmetrics, another approach to model physics systems. Application on solar panel behaviour. Advantages and complementarities with the physic’s approach. - Leila, Ouzeri (My University, 2021)
The aim of this work is to present two different approaches for modeling a photovoltaic panel (PV) fully illuminated. Generally, the physic’s model (White box) takes into account the physic, electronic and energetic behavior of different compound of the system’s model, as function of the solar irradiance and operating temperature. The statistician model (Black box) using the Design of Experiment method considers a physical system as a black box with various inputs (factors) and outputs (responses). Each approach has specific advantages, they are complementary.
Supplemental Materials: https://osf.io/tj7kn/
Keywords: Physicsmetrics; solar panel; physics approach